(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
The present study was conducted to explore the problems of sugarcane farmers in the selected areas of Natore district in Bangladesh. A total of 100 farmers were selected from Lalpur upazila of Natore district by using a simple random sampling technique. Data were collected through individual interviews during October to November, 2019 by using a structured interview schedule. Both descriptive and inferential statistics were used to analyze data. The majority of the sugarcane farmers (80%) had medium problems in sugarcane cultivation. Among twenty problems, difficulty in getting sugarcane setts was identified as the most critical one, followed by low market price of sugarcane. The least important problem faced by the farmers was lack of labour for sugarcane cultivation. Correlation analysis revealed that credit received, input availability, and extension media contact were significantly associated with the problems of sugarcane farmers. The study indicated some opportunities for the policymakers to address the dominant factors i.e. credit received, input availability, and extension media contact for increasing sugarcane production. Moreover, credit facilities, supply of inputs, proper training and access to extension services could play a vital role in lessening problems in sugarcane cultivation. Int. J. Agril. Res. Innov. Tech. 11(1): 101-108, June 2021